PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT BUDI KARYA MAJU - Budiyono; Suprihati (JURNAL ILMIAH EDUNOMIKA, 2026)
Effectiveness and efficiency are requirements for all organisations, in which human resource management plays a key role. Well-managed human resources will support the achievement of organisational goals. In this case, job satisfaction is a determining factor that increases employee enthusiasm, morale, discipline, and performance. This study aims to analyse the influence of work motivation and work environment on employee satisfaction at PT Bud Karya Maju. Using a saturated sampling method on 50 respondents and multiple linear regression analysis, the results of the study prove that work motivation and environment have a positive and significant influence on job satisfaction. Keywords : employee job satisfaction, work environment, and work motivation